ANALISIS BREAK EVEN POINT PADA USAHA KERIPIK SINGKONG “BAROKAH” DESA KARANG REJO KABUPATEN PESAWARAN - Suharto Suharto (Fakultas Teknik Universitas Tulang Bawang Lampung, 2017)
The purpose of an established business is to obtain profit or profit that can be used for survival. Likewise with the business of cassava chips